2023
DOI: 10.1101/2023.04.02.23288047
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Optimizing Individual Targeting of Fronto-Amygdala Network with Transcranial Magnetic Stimulation (TMS): Biophysical, Physiological and Behavioral Variations in People with Methamphetamine Use Disorder

Abstract: Background: Prior research on drug addiction has linked the frontopolar cortex and amygdala coupling to drug cue reactivity/craving. However, one-size-fits-all approaches for transcranial magnetic stimulation (TMS) over frontopolar-amygdala have led to inconsistent results. Objective: Here, we (1) defined individualized TMS target location based on functional connectivity of the amygdala-frontopolar circuit while people were exposed to drug-related cues, (2) optimized coil orientation for maximum electric fiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 93 publications
0
1
0
Order By: Relevance
“…Thanks to the advancements in brain mapping tools, it has been shown that there are two main sources of variation in response to brain stimulation (1) brain structure that changes electric field distribution patterns, and (2) brain state that affects responsiveness the received stimulation dose [72]. Recent clinical trials have emphasized the importance of personalized treatment approaches in neuromodulation for SUDs and showed that personalized stimulation parameters, guided by neuroimaging and electrophysiological data, might be able to enhance the precision and effectiveness of brain stimulation treatments [73,74].…”
Section: Individualized Vs One-size-fits-all Approachesmentioning
confidence: 99%
“…Thanks to the advancements in brain mapping tools, it has been shown that there are two main sources of variation in response to brain stimulation (1) brain structure that changes electric field distribution patterns, and (2) brain state that affects responsiveness the received stimulation dose [72]. Recent clinical trials have emphasized the importance of personalized treatment approaches in neuromodulation for SUDs and showed that personalized stimulation parameters, guided by neuroimaging and electrophysiological data, might be able to enhance the precision and effectiveness of brain stimulation treatments [73,74].…”
Section: Individualized Vs One-size-fits-all Approachesmentioning
confidence: 99%